Are Customs Unions Economically Sensible in the Commonwealth of Independent States - Michalopoulos, Constantine (Other papers, 2004)
The twelve members of the Commonwealth of Independent States established a Free Trade Area to help maintain trade among each other. More recently, Belarus, Kazakstan, the Kyrgyz Republic and Russia agreed, in principle, to establish a Customs Union (CU). The paper concludes that the dynamic effects of the CU (and Free Trade Area) are likely to be negative because it would tend to lock the countries into the old technology of the Soviet Union. The static effects are mixed but are adverse for countries that have liberal trade regimes compared to the common external tariff contemplated for the CU